FROM «GOOD GOVERNANCE» TO «GOOD GOVERNMENT»: FROM THEORETICAL CONCEPTS TO POLITICAL PRACTICES IN CONTEMPORARY RUSSIA - M. U. Tekeeva (Современная наука и инновации)
The article analyzes one of the Western governance concepts of the effective state formation titled «Good Governance». The principles of this concept are implemented in many contemporary states in the framework of raising efficiency of the politic and administrative governance. The article also looks into existing positive political practices formed in the West, outlines scenarios of their implementation in Russia. It emphasizes the elaboration of effective mechanisms of interaction between the state and society in the contemporary